2012
DOI: 10.1007/s10450-012-9392-4
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of γ-Al2O3 sorbents loaded with metal components and removal of thiophene from coking benzene

Abstract: Series sorbents of Cu, Zn, Ni, Ce and Ag metal components supported on γ -Al 2 O 3 carrier for removing thiophene from benzene were prepared by conventional and ultrasound-assisted incipient-wetness impregnation method. The static adsorption experiments were carried out in the thiophene-benzene solution with thiophene concentration of 500 mg/L. The results show that the desulfurization activity of all γ -Al 2 O 3 sorbents modified by different metal components obviously increase, among which the sorbent modifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 22 publications
0
15
0
Order By: Relevance
“…After that, a series of adsorbents which rely on π-complexation have been developed. Many studies have focused on dispersing these metals on various supports as π-complexation adsorbents, including zeolite, [30][31][32][33][34] alumina, [35][36][37] zirconia, 38 mesoporous silica, [39][40][41][42][43] β-cyclodextrin, 44 metal-organic frameworks (MOFs), 20,45 activated carbon, 46,47 and bentonite. 48 On the other hand, Song's group 49,50 tested various adsorbents under ambient conditions without H 2 gas and aimed at removing sulfur compounds from gasoline, jet fuels, and diesel fuels by a direct sulfuradsorbent interaction.…”
Section: Introductionmentioning
confidence: 99%
“…After that, a series of adsorbents which rely on π-complexation have been developed. Many studies have focused on dispersing these metals on various supports as π-complexation adsorbents, including zeolite, [30][31][32][33][34] alumina, [35][36][37] zirconia, 38 mesoporous silica, [39][40][41][42][43] β-cyclodextrin, 44 metal-organic frameworks (MOFs), 20,45 activated carbon, 46,47 and bentonite. 48 On the other hand, Song's group 49,50 tested various adsorbents under ambient conditions without H 2 gas and aimed at removing sulfur compounds from gasoline, jet fuels, and diesel fuels by a direct sulfuradsorbent interaction.…”
Section: Introductionmentioning
confidence: 99%
“…The peaks at 1636 cm À1 and 1447 cm À1 pertain to C-C stretching vibrations and C]C stretching vibrations of the thiophene ring, 21 respectively. 21,31 The FT-IR spectra of the P3MT/CeY composites present very different peak results to those discussed previously. 21,31 The bands around 708 cm À1 and 821 cm À1 belong to out-of-plane C-H deformation of a and b positions of 3MT, respectively.…”
Section: Composition and Structural Characteristics Of The Samplesmentioning
confidence: 70%
“…In order to calculate R A , the bands around 797 cm À1 and 1447 cm À1 were deconvoluted as show in Fig. 21,31 Sample conductivity was studied using a ZC-36 ohmmeter (Shanghai Qiangjia Electrc Co., Ltd., China). The bands around 708 cm À1 and 821 cm À1 belong to out-of-plane C-H deformation of a and b positions of 3MT, respectively.…”
Section: Characterization Of the Samplesmentioning
confidence: 99%
See 1 more Smart Citation
“…The incorporation of metals such as Cu, Ni, Zn, Ag, Ce and Co [1,2,28,29] oxides such as Al 2 O 3 and TiO 2 [30][31][32][33][34], has received attention in desulfurization by adsorption, because of several possible interactions as much both the aromatic rings as with the heteroatom of sulfur (in the thiophenic derivatives), providing a greater selectivity for the sulfur compounds [35]. For example, the theoretical and experimental study of titanium oxide in the adsorption of thiophene demonstrated relatively weak and selective interactions between thiophene molecules and the metal oxide [36].…”
Section: Introductionmentioning
confidence: 99%